Sebaran Fraksi Sedimen Dasar Permukaan di Perairan Pantai Pulau Topang Provinsi Riau - Hade Mulyadi; Mubarak Mubarak; Dessy Yoswaty (Dinamika Lingkungan Indonesia, 2015)
A study was conducted in december 2013 in coastal waters Topang Island RiauProvince, with a view to learn the environmental conditions under the deposition ofoceanography and physics. The method used is a method of surveys carried out at 12 stationswithout repetition and 2 times repetition on calculations of the quality of the waters .Theresults of research shows that bottom sediment surface waters can be grouped into threefaction sediment is sandy mud , muddy sand and sand .Sand faction dominating at anyresearch station with type 2 is sand and muddy sand .Based on the parameter of sediment asthe diameter of average (Mz), sorting ( ), skewness (Sk1) and kurtosis (KG), physicaloceanographic conditions in Western and Eastern parts of the island tend to be stablecompared to the North and South. Current speed of surface affect the distribution of thebottom sediment surface.